Trade Liberalization, Economic Activity, and Political Violence in the Global South: Evidence from PTAs - Francesco Amodio; Leonardo Baccini; Giorgio Chiovelli; Michele Di Maio (Institute of Labor Economics (IZA), 2023)
This paper investigates the impact of agricultural trade liberalization on economic activity and political violence in emerging countries. We use data on all Preferential Trade Agreements (PTAs) signed between 25 low- and middle-income countries and their high-income trade partners between 1995 and 2013. We exploit the implied reduction in agricultural tariffs over time combined with variation within countries in their suitability to produce liberalized crops to find that economic activity increases differentially in affected areas. We also find strong positive effects on political violence, and present evidence consistent with both producer- and consumer-side mechanisms: violence increases in more urbanized areas that are suitable to produce less labor-intensive crops as well as crops that are consumed locally. Our estimates imply that economic activity and political violence would have been around 2% and 7% lower, respectively, across countries in our sample had the PTAs not been signed.
Keywords: D22; D24; F51; N45; O12; 330; political violence; trade; agriculture; preferential trade agreement